KONSEP ANGELOLOGI DALAM KITAB SAMARKAND : (Solusi Alternatif Problem Lingkungan) - Muhammad Nasrudin Baihaqi,; Muhammad Ainul Yaqin,; Muhammad Mubarak,; Roch. Aris Hidayat, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
Angelology is the study of Angels and their relationship to the universe. The concept became part of the nature of Islamic thought, both among philosophers and theologians. One of the classical theological literature in the form of Codex entitled Kitāb discusses angelology. The function of Angelology is to provide an alternative knowledge in understanding the universe before modern science so that the view of the sacredness of nature is still maintained. Environmental degradation today is the result of the secularization of the cosmos caused by modern science claiming a single interpretation of nature. This paper seeks to explore aspects of Angelology in Kitāb Samarkand and contextualize it as an alternative solution to current environmental problems. The method used is qualitative with literature research using hermeneutics analysis. The result of this writing is that the Angels Kitāb Samarkand can be interpreted according to philosophical and theological views. Angelology in the book can raise awareness about the need for the sacralization of nature as an effort to prevent environmental damage caused by modern science.